BELANJA PEMERINTAH DAN PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT - Amrillah; Irwan, Muhammad; Firmansyah, Muhammad (Universitas Mataram, 2023)
West Nusa Tenggara Regional Government expenditure is still dominated by personnel expenditure and low capital expenditure, as well as economic growth achievements that are not optimal. Therefore, this study aims to examine the impact of government spending on economic growth in West Nusa Tenggara Province. This research uses dynamic panel data regression with a generalized method of moments (Sys-GMM) system approach to identify the impact of government spending on economic growth. The research results show that economic growth is influenced by personnel spending, goods and services spending, capital spending, and previous growth rates, but in different directions. This study also found that there has been a convergence of economic growth between districts and cities.